Glucocorticoids, Sex Hormones, and Immunity - Bereshchenko, Oxana; Bruscoli, Stefano; Riccardi, Carlo (Frontiers in Immunology, 2018)
Glucocorticoid hormones regulate essential body functions in mammals, control of cell metabolism, growth, differentiation and apoptosis. Importantly, they are potent suppressors of inflammation, and multiple immune-modulatory mechanisms involving leukocyte apoptosis, differentiation and cytokine production have been described. Due to their potent anti-inflammatory and immune-suppressive activity, synthetic glucocorticoids are the most prescribed drugs used for treatment of autoimmune and inflammatory diseases. It is long been noted that males and females exhibit differences in the prevalence in several autoimmune diseases (AD). This can be due to the role of sexual hormones in regulation of the immune responses, acting through their endogenous nuclear receptors to mediate gene expression and generate unique gender-specific cellular environments. Given the fact that glucocorticoids are the primary physiological anti-inflammatory hormones, and that sex hormones may also exert immune-modulatory functions, the link between glucocorticoids and sex hormones may exist. Understanding the nature of this possible crosstalk is important to unravel the reason of sexual disparity in autoimmune diseases and to carefully prescribe these drugs for the treatment of inflammatory diseases. In this review, we discuss similarities and differences between the effects of sex hormones and glucocorticoids on the immune system, to highlight possible axes of functional interaction.